Histopathological Pattern of Salivary Gland Tumors - Shrestha, S; Pandey, GK; Pun, CB; Bhatta, R; Shahi, R (Journal of Pathology of Nepal, 2014)
Background: The tumors of the salivary glands are uncommon head and neck neoplasms. The aim of this study was to evaluate the relative frequencies, types, site distribution and the histopathological features of salivary gland tumors. Materials and Methods: This was a retrospective study of 176 cases of salivary gland tumors collected from medical record section and department of pathology at B.P.Koirala Memorial Cancer Hospital from Jan. 2005 to Dec. 2010. Tumors were analyzed based on demographics, anatomic location and histopathological type. Results: Out of 176 cases, 66 (37.5 %) were benign and 110 (62.5 %) were malignant with M:F ratio of 1.7:1. The mean age observed was 44.76 years with age range of 12 to 75 years. Pleomorphic adenoma was found to be the commonest benign tumor (72.7 %), followed by Warthin tumor (15.1%), monomorphic adenoma (3.0 %) and basal cell adenoma (3.0 %). The mucoepidermoid carcinoma was the most common malignant tumor (38.1 %), followed by adenoid cystic carcinoma (25.4%), acinic cell carcinoma (10.9%), adenocarcinoma NOS (6.3%), carcinoma ex pleomorphic adenoma (5.4%) and unclassified malignant tumor (4.5 %). Parotid was the most common site for the location of tumors (70.4%) followed by submandibular (19.3%) and minor salivary glands (10.2 %). Conclusion: Pleomorphic adenoma was the commonest salivary gland tumor observed in both sexes. Mucoepidermoid carcinoma was the most common malignant salivary gland tumor. The parotid gland was the most common site of origin in both benign and malignant tumors. DOI: http://dx.doi.org/10.3126/jpn.v4i7.10291 Journal of Pathology of Nepal (2014) Vol. 4, 520-524